Silicon nanowires, cryogenic control and radio-frequency read-out for quantum devices - Schupp, F (2018)
For the last two decades research on grown nanowires has been motivated by their potential application as efficient transistors, sensors and building blocks of quantum information processing architectures. While these applications can benefit from quantum effects, such as tunneling and quantum interference, the integration of bottom-up grown nanowires into larger circuits is technologically challenging. Top-down fabricated nanowires, that recently became available due to progress in semiconductor fabrication, provide a means of overcoming this barrier. In combination with silicon spin qubits, they could enable a fully integrated quantum processor with silicon nanowire control electronics that comply with the cooling requirements in a cryogenic environment. I will present silicon nanowire transistors that were fabricated using CMOS-compatible processing and operate at room temperature as well as in the cryogenic regime. With a diameter of only 8 nm, the nanowire devices exhibit excellent electrostatic control of the channel and show evidence for one dimensional transport. Transport in these nanowires is dominated by scattering off dopants and off the nanowire walls rather than off the rough nanowire surface or other surface defects that often dominate in nanowire devices. Optimized nanowires with lower doping and shorter channels could therefore enable ballistic cryogenic CMOS with ultra low heating in a cryogenic quantum processor. In addition to DC experiments, I will use a measurement technique where the impedance of a quantum device in a resonant circuit can be inferred from the reflection of radio-frequency signals. The sensitivity to a changing device impedance is improved via in-situ impedance matching of the resonant circuit to the measurement electronics. As a result charging events in a silicon nanowire device can be detected with a good charge sensitivity. In case the quantum device requires small input powers, for example if measurement back-action is significant, further improvement is achieved by employing a low noise SQUID amplifier. The measured sensitivity to changes in the quantum capacitance enables the read-out of a singlet-triplet qubit much faster than the typical decay time of the quantum state. Since the technique does not require additional sensing devices and the read-out circuit can be connected directly to a gate electrode of the qubit, this type of read-out is promising for scalable quantum information processing architectures.